INFLUÊNCIA DE FIBRAS DE POLIPROPILENO NA PROPRIEDADE DE ADERÊNCIA EM ARGAMASSAS DE REVESTIMENTO - Gasques, Elisabet; Oyamada, Giovanna; Resende, Andréa; Piaseck, Alice; Gasques, Ana (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Mortar coatings comprise several functions, however, it's also associated to pathologies. Cracking and loss of adhesion of a mortar coating may be associated by the retraction effects. In order to solve those problems, fibers can be incorporated in the mortar, which tends to act by making it difficult to propagate cracks, helping in tension spreading. In this way, this paper aims to evaluate the influence from the polypropylene’s fiber on adhesion’s property of coating mortar. For the evaluation, three polypropylene fiber concentrations (500, 1000 and 1500 g/m[1]) were tested in a mixed mortar of cement and lime 1: 0.5: 6 (by volume). The mortars were applied in two thicknesses, 30 and 50 mm, on the surface of the concrete block prisms and the properties measured were density, consistency index, water retention, the normal stress supported on the flexure and compression tests and adhesion strength. It has been verified that the coating with polypropylene's fiber presented higher adhesion strength for both thickness. Also the values of the mechanics behavior for both concentrations, 1000 and 1500 g/m3, were very similar. To conclude the 1000 g/m3 presented higher resistance with lower consumption becoming the best option.